A new computation algorithm for a cryptosystem based on Lucas Functions - Othman, Mohamed; M. Abulhirat, Esam; Md Ali, Zulkarnain; Md. Said, Mohamad Rushdan; Johari, Rozita (Science Publications, 2008)
Most of public-key cryptosystems rely on one-way functions. The cryptosystems can be used to encrypt and sign messages. The LUC Cryptosystem is a cryptosystem based on Lucas Functions. The encryption process used a public key which was known publicly and the decryption used a private key which was known only by sender and receiver of the messages. The performance of LUC cryptosystem computation influenced by computation of Ve the public key process and Vd the private key process. Very large scales of computations and timing overhead involved for large values of e and d. We are presenting the so-called Doubling with Remainder compared to the existing technique. It shows better performance in LUC computations by reducing time consumed in its computations. The experimental results of existing and new algorithm are included.